Efeito agudo do número de séries de exercícios do Método Pilates nas respostas cardiovasculares em mulheres hipertensas - Chagas, Jocarla da Conceição (2016)
Introduction: The Pilates method, featured as a strength exercise, it has proven beneficial in muscle strengthening and physical conditioning and reducing percentage of body fat. However, few studies have investigated its effect on the cardiovascular responses, and present lack as regards the training variables. Objective: To evaluate the acute effects of the number of sets exercises of Pilates method on cardiovascular responses in hypertensive women. Methods: Seventeen women, eight hypertension (59 ± 1.7 years) and nine normotensive (57 ± 1.6 years) were submitted to two Pilates sessions, consisting of 15 exercises with one or three series, both with 10 repetitions, interval of one minute rest between sets and moderate intensity. Measurements of blood pressure (BP) and heart rate (HR) were taken for 20 minutes previously to workout and 60 minutes after the sessions. Results: The between groups analysis showed that the number of sets does not interfere in BP responses, HR and double product (DP). The intragroup analysis showed a reduction of HR in all groups. In the hypertensive group was observed reduction in PD after both Pilates sessions, and normotensive group only after the session with a sets. Conclusion: The variables shows that perform one or three series of Pilates exercises does not interfere the cardiovascular responses after an exercise session.